2018
DOI: 10.1016/j.psychres.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

The tangled roots of inner speech, voices and delusions

Abstract: The role of inner speech in the experience of auditory verbal hallucinations (AVH) and delusions remains unclear. This exploratory study tested for differences in inner speech (assessed via self-report questionnaire) between 89 participants with psychosis and 37 non-clinical controls. We also tested for associations of inner speech with, i) state/trait AVH, ii) AVH-severity; iii) patients' relations with their voices, and; iv) delusion-severity. Persons with psychosis had greater levels of dialogic inner speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 69 publications
(99 reference statements)
3
17
0
1
Order By: Relevance
“…Overflowing and Distracting: Sz-AVH subjects may experience more intrusions in IS, and this would negatively affect their performance in verbal, inhibition, shifting, and planning tasks. For instance, in the study conducted by Alderson-Day et al (2014) , vulnerability to AVH experiences correlates with the presence of other people in IS (see also de Sousa et al, 2016 ; Rosen et al, 2018 ). This characteristic may in turn be connected with a higher degree of interference with task completion, as the presence of other people in IS would arguably represent a major distracting factor.…”
Section: Executive Functions and Inner Speech In Sz-avhmentioning
confidence: 99%
“…Overflowing and Distracting: Sz-AVH subjects may experience more intrusions in IS, and this would negatively affect their performance in verbal, inhibition, shifting, and planning tasks. For instance, in the study conducted by Alderson-Day et al (2014) , vulnerability to AVH experiences correlates with the presence of other people in IS (see also de Sousa et al, 2016 ; Rosen et al, 2018 ). This characteristic may in turn be connected with a higher degree of interference with task completion, as the presence of other people in IS would arguably represent a major distracting factor.…”
Section: Executive Functions and Inner Speech In Sz-avhmentioning
confidence: 99%
“…Our previous research has shown that absorption is more prevalent and intense in participants with psychosis when compared to non-clinical controls, and was significantly associated with hallucinations and delusions ( 15 ). We have also previously shown that dialogic inner speech is associated with psychosis ( 24 ). In this study we report that in participants with psychosis, dialogic inner speech and evaluative and motivational inner speech were associated with all factors of absorption whereas condensed inner speech was associated with imaginative involvement.…”
Section: Discussionmentioning
confidence: 81%
“…Inner-speech is defined as a conversation that occurs internally. Inner-speech in participants with psychosis has been shown to be differentially expressed in the presence of sensory and perceptual experiences, when compared to non-clinical controls ( 23 , 24 ). Theoretically, Dialogical Self Theory (DST), posits self as the narrator in which the “I-position” bridges both inner dialogue/speech with oneself and outer dialogue with others ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…24. For theoretical reasons, the scores on the SAS and DA subscales were used in the analysis of the results and not the total scores on each of them (Perona‐GarcelĂĄn et al, ; Rosen et al, ). The first two hypotheses were studied using the Pearson's correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%